2014
DOI: 10.1108/cr-06-2013-0063
|View full text |Cite
|
Sign up to set email alerts
|

Variables influencing expatriate learning and organizational learning

Abstract: Purpose -The purpose of this paper is to identify the variables that influence the international assignment -expatriate learning relationship and the expatriate learning -organizational learning relationship. Design/methodology/approach -The paper contains a literature review of the research on expatriates' learning and organizational learning Findings -The paper provides an integrative framework that identifies the moderating variables that influence both the relationship between the expatriate international … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
6
0
3
Order By: Relevance
“…In the context of an MNC, a particularly interesting factor that could alter individuals' work environment and subsequently create opportunities for skill development is the nature and context of overseas assignments (Dragoni et al 2014). Past studies have delved into the learning effects of international assignments on individual employees (for a review, see Barakat and Moussa 2014), with a specific focus on the long-term phenomenon of expatriation (Bonache et al 2010;Collings et al 2009;Edström and Galbraith 1977). These studies have shown that MNCs extensively use expatriates and international assignees alike to foster knowledge transfer and organizational learning (Nery-Kjerfve and McLean 2012).…”
Section: Opportunity and Absorptive Capacitymentioning
confidence: 99%
“…In the context of an MNC, a particularly interesting factor that could alter individuals' work environment and subsequently create opportunities for skill development is the nature and context of overseas assignments (Dragoni et al 2014). Past studies have delved into the learning effects of international assignments on individual employees (for a review, see Barakat and Moussa 2014), with a specific focus on the long-term phenomenon of expatriation (Bonache et al 2010;Collings et al 2009;Edström and Galbraith 1977). These studies have shown that MNCs extensively use expatriates and international assignees alike to foster knowledge transfer and organizational learning (Nery-Kjerfve and McLean 2012).…”
Section: Opportunity and Absorptive Capacitymentioning
confidence: 99%
“…They are also required to create the new career paths for the repatriates where they can best utilize their newly acquired knowledge, skills and expertise which will not only enhance the motivational level of the repatriates but also will enhance the organizational performance (Kjerfve and Gary, 2011). Organizational Management should pay attention on the repatriation process carefully by offering them such new job placements on their return the home country that the skills and expertise acquired by these repatriates could be properly procured and organizational learning could be intensified (Barakat and Moussa, 2014). If the organizations do not plan proper career paths for the repatriates it may turn the repatriates to dissatisfaction on their arrival back to the home country (Bossard and Peterson, 2005).…”
Section: Job Placementmentioning
confidence: 99%
“…Expatriação e Processos de Aprendizagem Organizacional: um estudo de casos múltiplos. Revista Eletrônica de Ciência Administrativa, 18( 2 prática do cotidiano é suprida no momento em que ele busca e aproveita outras formas de aprendizagem, tais como a prática do feedback, interação, colaboração, networking e observação/modelos, com características mais informais e sociais, associadas ao conhecimento tácito dependentes do contexto (Bonache et al, 2001, Nicolini et al, 2003Antonello, 2011;Barakat & Moussa, 2014). Por último, tem-se o desenvolvimento das habilidades culturais, necessárias para se trabalhar e viver em outros países e, principalmente, para entender como agem empregados e clientes do país estrangeiro, o que pode estar associado às mudanças de perspectiva e de identidade, bem como à aprendizagem da vida na expatriação (González & Oliveira, 2011;Gallon & Scheffer, 2015).…”
Section: Esquema Conceitualunclassified
“…A expatriação pode ser usada como um recurso efetivo de desenvolvimento pessoal e profissional que promove a aprendizagem do indivíduo, contribuindo para a organização. Constatou-se que a expatriação propiciou uma melhora na aprendizagem no contexto organizacional através do aprimoramento dos conhecimentos individuais pela experiência da expatriação, sob um enfoque social e cultural (Antonello, 2011;Barakat & Moussa, 2014). Porém, as organizações devem estar atentas não apenas à implementação da estratégia de expatriação, mas, principalmente, ao acompanhamento do processo (Vianna & Souza, 2009;Gallon & Antunes, 2013;Gallon & Bittencourt, 2016).…”
Section: Considerações Finaisunclassified